The Venture bros. Season five [videorecording (DVD)] - Warburton, Patrick; Sinterniklaas, Michael; Urbaniak, James, 1963-; McCulloch, Christopher ([publisher not identified], 2014)
Releasing with all eight episodes from Season five and packed with special features, fans will be thrilled when they watch Hank, Dean, Doctor Venture, and Brock as they are pushed in fun and unpredictable new directions.